LAJU PENDINGINAN PENGELASAN BAJA CARBON SEDANG PADA TEMPERATUR LINGKUNGAN BERBEDA - R. N. Akhsanu Takwim; Kris Witono; Pondi Udianto (INFO-TEKNIK, 2020)
The quality of welding results is influenced by the shape of the microstructure of the welding material especially in the HAZ region. The shape of the welding microstructure is largely determined by the cooling rate of the weld material. The cooling rate of the weld is greatly influenced by the heat input from the arc and the ambient temperature. This study aimed to determine the effect of different environmental temperatures on the cooling rate of welding results. Welding of GMAW fillets on medium carbon steel plates S50C, with variations in welding currents 90 A, 100A and 110A and carried out at variations in environmental temperature of 15oC, 10oC and 5oC. Temperature data on the middle, welding part is taken with a digital thermometer to compare the effect of each variable. The test results show that the greater the welding current, the slower the cooling rate. Similarly, an increase in ambient temperature causes a decrease in the weld metal's cooling rate.